Wspólne przedsięwzięcie w standardach rachunkowości - Tatarska, Marzena (Joint Venture in Accounting Standards, 2007)
This article presents the problem of adjusting Polish accounting standards to International Accounting Standards in the scope of joint venture. The Accounting Act defines joint control and jointly controlled entities. International Accounting Standard Financial Reporting of Interest in Joint Ventures defines additionally jointly controlled activities and jointly controlled assets. The article shows the difference between the Polish and international accounting standards concerning the issue of joint ventures presentation and valuation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 163-172